2021
DOI: 10.1016/j.nrleng.2021.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Three-month functional prognosis of patients hospitalised due to acute ischaemic stroke in Aragon: regional analysis of the impact of COVID-19

Abstract: Introduction The COVID-19 pandemic has had an impact on ischaemic stroke management, with a reported decrease in hospital admissions, and even disruptions in healthcare and increased in-hospital mortality. However, there is a lack of evidence on the impact of the pandemic on functional prognosis. The aim of this study is to analyse the effect of the COVID-19 pandemic on the 3-month functional outcomes of patients hospitalised due to acute ischaemic stroke in Aragon (Spain). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…The number of patients with favorable outcome was significantly less during COVID whether at discharge or at 3 months follow-up. Contrary to our findings, other studies found no significant difference in the frequency of mRS (0–2) at discharge between the two periods [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The number of patients with favorable outcome was significantly less during COVID whether at discharge or at 3 months follow-up. Contrary to our findings, other studies found no significant difference in the frequency of mRS (0–2) at discharge between the two periods [ 34 , 35 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A study in the Aragon region of Spain reported that the functional outcome at three months during the pandemic was not significantly different from that in the pre-pandemic. 18) A comprehensive stroke center in Japan reported similar results regarding the discharge outcome. 19) On the other hand, clinical outcomes were less favorable on discharge and at three months in a cross-sectional, observational, and retrospective study in which eight countries participated by providing data from the stroke database.…”
Section: Discussionmentioning
confidence: 74%